The Analysis on Leading industries in Central Java Province - Irmawati, Setyani (Semarang State University, 2015)
The purpose of this research is for identifying the types of industriesthat become leading industries in Central Java Province. The methods, used are LQ (SLQ and DLQ) and Shift Share. The result of this research shows that the the leading industries in Central Java Province are beverage industry, tobacco processing industry, textile industry, apparel industry, wood industry, printing industry, furniture industry and other processing industries.In the future, the development of the industry should not only focus on the leading industriesÂ but also onnon-leading industries, so that the non leading industries will not be left behind.